Exploring Factors Affecting English Language Learning for Members of the National Police (2024)
Learning a foreign language is a challenging task for most people. These challenges have been reported and reviewed by the global literature for decades. Numerous elements influence the journey of acquiring a foreign language. These encompass factors such as one's mindset, self assurance, drive, length of language exposure, classroom ambiance, surroundings, family context, and the presence of proficient educators (Ushioda, & Dörnyei, 2017)